Life Struggle Of Mikael Blomkvist Reflected The Girl With The Dragon Tattoo Novel (2008) : An Individual Psychological - Purnomosari, Desi, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S. M. Hum (2014)
The reseach paper aims at knowing life strugle of Mikael Blomkvist in The Girl with the Dragon is a novel by Stieg Larsson which is analyzed by using individual psychological. The objective of the research is to analyze the novel based on the structual elements of the novel and to analyze the novel based on individual psychological proposed by Alfred Adler. The type of this research is descriptive qualitative. Data of the reseacrh are taken from. The primary data of research is The Girl with the Dragon Tattoo novel. The secondary data of the research are taken from books, other source and website that related to the study. The method to analize of this data is descriptive analysis. The research show that moral massage The Girl with the Dragon Tattoo novel by Stieg Larsson that " There is pain there is no gain" it is an action taken by everyone to be able to struggle through everyting occupation that they do Based on the individual psychological analysis, the author illusrates a psychological phenomenon in which an individual should work hard in order to meet his need. The psychological phenomenon is delivered by the struggle of Mikael blomkvist as a major character in The Girl with the Dragon Tattoo novel has many manners for his life.